Pengaruh Kecemasan Matematika terhadap Hasil Belajar Siswa SMP - Rizka Siti Alifa; M. Hasbi; Usman Usman (Jurnal Peluang, 2023)
Mathematics often evokes fear in students, leading to anxiety when facing math problems. Understanding the phenomenon of math anxiety is a crucial aspect to consider. In this study, researchers employed a quantitative approach to examine math anxiety's impact on student learning outcomes at one of the junior high school in Sigli, Aceh, Indonesia. The population of interest consisted of all students enrolled at the selected school, with the sample comprising all eighth-grade students selected through a simple random sampling technique. A simple linear regression analysis was conducted to investigate the relationship between variables, resulting in the following equation. Furthermore, a rank-Spearman correlation test yielded a correlation coefficient of r = -0.6. The data analysis revealed a significant influence of math anxiety on the student learning outcomes.